Flame Text Algorithm for Storing Secure Information in Cloud (International journal of innovative technology and exploring engineering, 2019)
In the present age, we are putting away our information in the cloud; however, there is a great deal of security requests. So as to improve the security, our venture proposes another encryption calculation called Flame Text Algorithm and furthermore 3 stage check forms takes places for putting away the Electronic Health Records (EHR) data in the cloud. At first, the medicinal expert people can enter their username and the secret key. On the off chance that the client is legitimate and login acknowledged methods, at that point the subsequent stage unique mark verification process takes places. In the unique mark Authentication process the medicinal specialist individual unique finger impression is checked, on the off chance that it is confirmed effectively, at that point a verification code will be sent to the mail id of the specific individual. At that point the individual needs to sign in their very own mail id for the check code. After unique finger impression confirmation, an alarm input box will show up, in that the individual needs to put the verification code to transfer or view the reports of Electronic Health Records of patients. After validation code effective then the therapeutic individual can transfer the archives of their worry tolerant subtleties in the cloud. Before putting away the information in the cloud an encryption procedure happens. This is the new Algorithm system where the security can be more on the grounds that the encryption and decoding take puts similarly. At that point the client can view and impart their subtleties to someone else too. The main feature of this project is the use of own Encryption and Decryption Algorithm (FLAME TEXT) which will secure our data more compared to other techniques.